Basic studies conducted to the optimization of a mass rearing system for Typhlodromalus tenuiscutus (Acari: Phytoseiidae), a predator of cassava mites - OSORIO-RÍOS, LILIANA; CUÉLLAR-JIMÉNEZ, MARÍA ELENA; SMITH, LINCOLN (Revista Colombiana de Entomología, 1999)
For a number of years, the personnel of the acarology biological control project at CIAT has developed and adapted various systems for mass-rearing phytoseiid miles, one of which is that of Mesa and Bellotti (1987). This is a simple system using cassava leaves infested with phytophagous miles to feed phytoseiids in enclosed plastic containers. Although data on the production rate of this system have been collected. a population dynamic mode! does not exist. which could help to plan and optimize production. As a basis for developing a computer model we have collected data on development time, fecundity. prey consumption. and production of progeny in Mesa-Bellotti cultures of the phytoseiid Typhladromalus tenuiscutus. In all the experiments cassava leaves infested with Mononychellus caribbeanae were used to provide prey. The experiments on demography and prey consumption were conducted on leaf disks in plastic vials making daily observations. The experiment on colony production was initiated with 50, 100, and 200 females, and adult females were harvested weekly for 8 weeks. Development time from egg to adult was 6.0 days at 25° C. 675 of the eggs reached adulthood, the sex ratio was 70% females, and the average longevity of adult females was 30.8 days. The periods of preoviposition. oviposition and postoviposition 1.8. 16.4 and 4.6 clays, respectively, and average fecundity was 29.3 eggs. The population parameters were: intrinsic rate of natural increase r0= 0.20, the net rate of increase = 1.23. net reproductive rate Ro = 17.8, mean generation time T = 14.1 clays. y doubling time TD = 3.3 days. Eggs were the preferred stage of prey for T tenuiscutus larvae. and larvae were preferred by the other developmental stages. The average consumption of prey during development from larva to adult was 6.3 eggs, 16.2 larvae. 4.2 nymphs, and 1.7 adults of M. caribbeanae. The highest production of females from Mesa-Bellotti cultures was from those initiated with 100 females. the least from those started with 50 females and those initiated with 200 fluctuated the most.